THE EVOLUTION OF THE CONCEPT OF CONSTRUCTIVISM IN THE TEACHING AND LEARNING PROCESS (Ustozlar uchun, 2026)
This article rely on the principles of constructivism and various consequences of constructivism in education and learning was embraced. The research, thus, determined that educator must contemplate their methods to incorporate these concepts into their efforts and that constructivist educators must consider their methods to implement these concepts in their roles and that Constructivist educators motivate learners to consistently evaluate how the task aids in their understanding.